Distinguishing quantum dot-like localized states from quantum well-like extended states across the exciton emission line in a quantum well. (16th February 2018) - Bhuyan, Sumi; Mondal, Richarj; Pal, Bipul; Bansal, Bhavtosh
Abstract: We have closely examined the emission spectrum at the heavy-hole exciton resonance in a high-quality GaAs multi-quantum well sample using picosecond excitation-correlation photoluminescence (ECPL) spectroscopy. Dynamics of the ECPL signal at low and high energy sides of the excitonic photoluminescence (PL) peak show complementary behavior. The ECPL signal is positive (negative) below (above) the PL peak and it changes sign within a narrow band of energy lying between the excitonic absorption and emission peaks. The energy at which this sign change takes place is interpreted as the excitonic mobility edge as it separates localized excitons in quantum dot-like states from mobile excitons in quantum well-like states.